AND THEMATIC INSTRUCTIONAL FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Siahaan, Parsaoran; Lyliyasari, Ms (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2010)
This research, is part of a research on the development of a learning to improve mastery concept of science and the instructional. The learning model in this research integrate two courses with different subject and different semester in two PGSD of several campuses of an university of teacher training.Â  PGSD-X, which is in the same city with the University and PGSD Y in other city at the same province. Subject of the research consisted of 25 prospective teacher students in PGSD X and 26 prospective teacher students in PGSD-Y. Scenario of learning was done in 4 phases, namely: (1) modeling phase, (2) discussions phase, (3) enrichment phase, and (4) peer teaching phase. The learning topics is the integration of foodâs topic and thematic. The data was collected before learning (pre test) and after learning (post test). Data analysis was done by calculating the normalized gain from Hake <g>. The results from PGSD-XÂ  obtainedÂ  <g>=0,72Â±0,07 in the mastery of foodÂ  andÂ  <g>= 0,70Â±0,14 in thematic. The results from PGSD-Y obtained <g>=0,66Â±0,10 in the mastery of food and <g>=0,53Â±0,20 in thematic. The results could be concluded that the ability of prospective teachers in the PGSD X better than PGSD âY in mastery of food concept and thematic instructional.Â Key words: learning model, prospective teachers, food, thematic